Metformin regulates ovarian angiogenesis and follicular development in a female Polycystic Ovary Syndrome rat model - Di Pietro, Mariana (2015)
Polycystic ovary syndrome (PCOS) is a frequent pathology that affects more than 5% of women of reproductive age. Among other heterogeneous symptoms, PCOS is characterized by abnormalities in angiogenesis. Metformin has been introduced in the treatment of PCOS to manage insulin resistance and hyperglycemia. Besides its metabolic effects, metformin has been shown to improve ovulation, pregnancy and live birth rates in PCOS patients. In the present study, we used a dehydroepiandrosterone-induced PCOS rat model to analyze the effect of metformin administration on ovarian angiogenesis. We found that metformin was able to restore the increased levels of vascular endothelial growth factor, angiopoietin (ANGPT)1, and ANGPT1/ANGPT2 ratio and the decreased levels of platelet-derived growth factor B and platelet-derived growth factor D observed in the dehydroepiandrosterone-treated rats. These effects could take place, at least in part, through a decrease in the levels of serum insulin. We also found an improvement in follicular development, with a lower percentage of small follicles and cysts and a higher percentage of antral follicles and corpora lutea after metformin administration. The improvement in ovarian angiogenesis is likely to restore the accumulation of small follicles observed in PCOS rats and to reduce cyst formation, thus improving follicular development and the percentage of corpora lutea. These results open new insights into the study of metformin action not only in glucose metabolism but also in ovarian dysfunction in PCOS women